Gambaran tingkat pengetahuan masyarakat terhadap kepatuhan protokol kesehatan pada masa pandemi COVID-19 di lingkungan V Kelurahan Malalayang I Barat Kota Manado - Anira U. Syariffudin; Frelly V. Kuhon; Dina V. Rombot (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2021)
Background: Coronavirus Disease-19 (COVID-19) is an infectious disease caused by a new type of corona virus that emerged at the end of 2019 in Wuhan, People's Republic of China (PRC) which cause a pandemic in almost all the countries. The total number of COVID-19 cases reported on August 19, 2021 was 209,201,939 cases with a death rate of 4,390,467 in 215 affected countries. Lack of knowledge will lead to the rapid increase in the number of COVID-19 cases, due to the massive spread of COVID-19 information and not all of the information is accurate. When people obtain wrong information, it will have a negative impact on people's behavior.Purpose: Knowing the level of public knowledge regarding compliance with health protocols during the COVID-19 pandemic.Methods: This study used a descriptive method with a cross sectional design which was carried out from September until November 2021. There were 99 samples that met the inclusion and exclusion criteria, which was obtained by using a simple random sampling technique. Results and Conclusions: The results of this study showed that: 1. 54.5% people at Environment V, West Malalayang I Village, Manado City, had a lack knowledge about COVID-19. 2. The compliance level on health protocols of the community at Environment V, West Malalayang I Village, Manado City, during the COVID-19 pandemic was 100.0%. Keywords: COVID-19, knowledge, health protocol